2023
DOI: 10.1002/jmv.29120
|View full text |Cite
|
Sign up to set email alerts
|

The association of sickle cell disorder with adverse outcomes in COVID‐19 patients: A meta‐analysis

Tianyi Liang,
Kaixin Guo,
Peng Ni
et al.

Abstract: The aim is to elucidate the relationship between sickle cell disorder and severe COVID‐19. We systematically searched the required articles in three electronic databases, extracting and pooling effect sizes (ES) and 95% confidence interval (CI) from each eligible study to evaluate the effect of combined sickle cell disorder on adverse consequences in patients with COVID‐19. This meta‐analysis included 21 studies. Sickle cell disease (SCD) was a risk factor for mortality (pooled ES = 1.70, 95% CI: 1.00–2.92, p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The analysis by Liang et al 1 provided evidence that patients with SCD are particularly vulnerable during the pandemic. The authors should be congratulated for their efforts to characterize the risk and fill the knowledge gaps around COVID-19 and SCD.However, we wish to emphasize a significant issue that could enhance the comprehensiveness of the study by Liang et al 1 The authors found that SCD significantly increased the risk of hospitalization (pooled odds ratio: 6.21) compared with other outcomes such as mortality (pooled odds ratio: 1.7) and intensive care unit (ICU) admission (pooled odds ratio: 2.29). 1 This highlights that hospitaliza-…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis by Liang et al 1 provided evidence that patients with SCD are particularly vulnerable during the pandemic. The authors should be congratulated for their efforts to characterize the risk and fill the knowledge gaps around COVID-19 and SCD.However, we wish to emphasize a significant issue that could enhance the comprehensiveness of the study by Liang et al 1 The authors found that SCD significantly increased the risk of hospitalization (pooled odds ratio: 6.21) compared with other outcomes such as mortality (pooled odds ratio: 1.7) and intensive care unit (ICU) admission (pooled odds ratio: 2.29). 1 This highlights that hospitaliza-…”
mentioning
confidence: 99%
“…However, we wish to emphasize a significant issue that could enhance the comprehensiveness of the study by Liang et al 1 The authors found that SCD significantly increased the risk of hospitalization (pooled odds ratio: 6.21) compared with other outcomes such as mortality (pooled odds ratio: 1.7) and intensive care unit (ICU) admission (pooled odds ratio: 2.29). 1 This highlights that hospitaliza-…”
mentioning
confidence: 99%
See 2 more Smart Citations